Efficient authentication protocol for secure multimedia communications in IoT-enabled wireless sensor networks - Mishra, Dheerendra; Vijayakumar, P.; Sureshkumar, Venkatasamy; Amin, Ruhul; Islam, SK Hafizul; Gope, Prosanta (Multimedia tools and applications, 2018)
In current times, multimedia application includes integrated sensors, mobile networks and Internet-of-Things (IoT) services. In IoT services, if more devices are connected without much constrains, the problem of security, trust and privacy remain a challenge. For multimedia communications through Wireless Sensor Network (WSN), sensor nodes transmit confidential data to the gateway nodes via public channels. In such an environment, the security remains a serious issue from past many years. Only few works are available to support secure multimedia communications performed in IoT-enabled WSNs. Among the few works, Kumari and Om recently proposed an authentication protocol for multimedia communications in IoT-enabled WSNs, which is applicable in coal mine for safety monitoring. The authors claimed in their work that their contributory protocol strongly withstands several security threats such as, user impersonation attack, sensor node impersonation attack, sensor node anonymity issue and others technical design issues. However, this article proved that Kumari and Om’s protocol has some design flaws and is susceptible to various security attacks including, user and sensor node impersonation attacks. As a remedy, a robust authentication protocol using smartcard is constructed to solve the security issues found in Kumari and Om’s protocol. The proof of correctness of mutual authentication is performed using the BAN logic model. In addition, our further security investigation claimed strong protection against known security attacks. Our protocol is analyzed comprehensively and compared against the similar protocols and the results showed that it is efficient and robust than earlier protocols.